Respostas

A melhor resposta!
2014-05-01T12:56:19-03:00
Δ = b² - 4ac
Δ = ( -7 )² - 4 * 3 * 2
Δ = 49 - 24
Δ = 25

x = -b ± √Δ
        2.a

x = -(-7) ± 5
       2.3
x =
± 5
        6

x' = 7 + 5 = 12 / 6 = 2

1 5 1
2014-05-01T12:57:49-03:00
A= 3  B= -7  C= 2
Δ= b² - 4ac
Δ= (-7)² - 4.3.2
Δ= 49 - 24
Δ= 25

X= -b+/-√Δ/2a
X= -(-7) +/-√25/2.3
X= 7 +/-5/6
X'= 7 + 5/6
X'= 12/6
X'= 2

Encontrado o resultado desejado, sigo abaixo com a continuação do cálculo.
X''=7-5/6
X"= 0,33

Xv= -b/2a
Xv= -(-7)/2.3
Xv= 7/6
Xv= 1,17

Yv= -Δ/4a
Yv= -25/4.3
Yv= -25/12
Yv= -2,08

Y= 2